Stage IV gastric cancer successfully treated by multidisciplinary therapy including chemotherapy, immunotherapy, and surgery: a case report - Makoto Kawamoto; Hideya Onishi; Norihiro Koya; Hiroyuki Konomi; Kenji Mitsugi; Risa Tanaka; Junichi Motoshita; Takashi Morisaki; Masafumi Nakamura (Surgical Case Reports)
Abstract Background The prognosis of stage IV gastric cancer (GC) still remains unfavorable. Multidisciplinary approaches should therefore be considered to improve the survival of patients with stage IV GC. We report here a case of primary GC with potentially unresectable metastasis, successfully treated by a multidisciplinary approach including chemotherapy, immunotherapy, and surgery. Case presentation A 74-year-old man presented with multiple left neck masses. Abdominal computed tomography showed a thickened gastric wall and multiple lymphadenopathies including left supraclavicular lymph node. Gastroenterological endoscopy revealed tumor lesions in the gastric cardia. Tumor biopsy indicated a pathological diagnosis of poorly differentiated adenocarcinoma. Open left cervical lymph node biopsy showed histological features identical with the gastric tumor, indicating left clavicle lymph node metastasis of GC. After 2 years of chemo-immunotherapy with S-1/CDDP, paclitaxel, and cytokine-activated killer cells, lesions other than the stomach lesion had regressed to undetectable on imaging studies. The patient then underwent laparoscopy-assisted total gastrectomy with Roux-en-Y reconstruction followed by adjuvant chemo-immunotherapy with paclitaxel and S-1 for 1 year, and immunotherapy with tumor lysate-pulsed dendritic cell-activated killer cells for 5 years. The patient remained well after 5 years and 6 months of follow-up, with no signs of recurrence. Conclusion Therapeutic combinations including immunotherapy may thus allow surgery to be performed in patients previously considered unsuitable for surgical intervention, potentially leading to a clinical cure, as in the current case.